The Role of Al-Falah Boarding School in Gender Segregation: An Analysis of the Separation of Men and Women in Islamic Education - Hafidzi, Anwar; Mohamed Ali, Mohd Hatta; Nurdin, Nurdin (Pusat Studi Gender dan Anak Universitas Islam Negeri Antasari Banjarmasin, 2023)
Abstrak: This research examines the role of Islamic boarding schools in gender segregation, specifically focusing on the separation of men and women in Islamic education. A case study was conducted at Al-Falah Boarding School in Banjarbaru, Indonesia, using a descriptive-qualitative approach. The main findings indicate that gender segregation at Al-Falah Boarding School has positive impacts on learning, such as creating a focused learning environment and facilitating memorization of study materials without distractions from the opposite gender. Gender-based learning has been implemented in the study of Islamic jurisprudence (fikih). The role of the boarding school in the development of this separation is deemed effective, as evidenced by the achievements in personal and environmental development.